The Effect of Macro-indicators and Profit Sharing on Mudharabah Deposits: Evidence from Indonesia - Stalia, Sela; Sunarsih, Uun; Nasution, Nursanita; Mustika, Maya; Ardheta, Preztika Ayu (Research of Islamic Economics, 2024)
This research seeks to ascertain how interest rates, GDP, and profit-sharing relate to mudharabah savings in Islamic commercial banks. This study employs a quantitative research design and measures its findings using a panel data regression approach. Sharia commercial banks that registered with the Financial Services Authority (OJK) between 2016 and 2020 make up the research population. There were 180 observations in total in this study because the sample was chosen using the purposive sampling method and included a total of nine Sharia commercial banks. This study employed secondary data, specifically quarterly financial reports. The study's findings demonstrate that mudharabah deposits benefit from interest rates. Mudharabah benefits from the amount of profit sharing. deposits. Mudharabah deposits are positively impacted by the GDP. It is well recognized that the amount of mudharabah savings is influenced by GDP, a measure of people's income. The managerial ramifications of how GDP, profit-sharing, and interest rates affect mudharabah deposits can be very significant in a financial context. Interest rates, income uncertainty, and risk management minutes. Profit sharing, compliance with Sharia principles, and product development and portfolio management.